Immigrant woman and gender violence: factors of vulnerability and social protection - Arnoso, M.; Arnoso, A.; Mazkiaran, M.; Irazu, A. (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
Even if violence against women is not exclusive of certain social and cultural groups, statistical studies in countries with a large immigration tradition mark a higher prevalence of this kind of violence in certain ethnic minorities (Cromwell & Burguess, 1996; Gondolf, 2002, 2005; Straus, Gelles & Steinmetz,1981) and in certain immigrant groups (Dutton, Orloff & Hass,2000; Raj & Silverman, 2002; Song, 1996). This over exposure of immigrant women to gender violence has also been comparedin our context, in a dynamic that seems to be intensifying ratherthan reducing itself. In 2009, more than twenty interviews with immigrant women victims of gender violence and professionalswere carried out in order to identify the factors that turn immigrantwomen into women especially vulnerable to male chauvinism, and how the social, sanitary, legal and police resources workin their interventions with this group. From the results of there search it was identifi ed that the economic situation of immigrantwomen, especially of those whose economic status depends on their husband and of those who are in an irregular situation,the precariousness of their social network and their difficulties in socio labor integration, housing field and access to basic social benefits seem to be factors that impede these women to get out ofthe violence circle. Despite the progress of the enforcement of the Integral Law and the subsequent law development in the Basque Country, the protection of the fundamental rights of immigrantvictims is still unequal to the one of national women, specifically in those factors that hamper the way of this group to social andhealth assistance, protection and justice.